Local anaesthesia systemic toxicity (LAST) – A stroke mimicker - Faiezah K; Tan, Toh Leong (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Local anaesthesia systemic toxicity (LAST) is an uncommon and a potentially life-threatening event that develops after peripheral nerve block. The cause may be multifactorial and may include the choice of drug, technique of block and individual patient risk factors. We report a case of a 55-year-old female who developed slurring of speech and quadriplegia after receiving a mixture of lignocaine and hydrocortisone through an intra-articular injection to the right shoulder. Neurological examination revealed hypotonia and absence of power (0/5) in all limbs. These toxic events may have resulted from an accidental intra-arterialor dural cuff injection of local anaesthesia or absorption from surrounding tissues. This case report demonstrated that an intra-articular injection in the shoulder may cause LAST and may be under-recognized as it can mimic stroke.